0692 Gender Dysphoria, Mental Health, and Poor Sleep Quality Among Transgender and Gender Non-Conforming Individuals: A Qualitative Study in New York City. (12th April 2019) - Harry-Hernandez, Salem; Reisner, Sari L; Schrimshaw, Eric; Radix, Asa; Mallick, Raiya; Hirisci, Ilgaz; Dubin, Samuel; Khan, Aisha; Duncan, Dustin T
Abstract: Introduction: A vast amount of research has demonstrated the numerous adverse health risks of short sleep duration and poor sleep health among the general population, and increasing studies have been conducted among lesbian, gay, and bisexual individuals. However, poor sleep health is disproportionately experienced by sexual and gender minority populations, and little research has examined sleep disparities or sleep quality among transgender and gender non-conforming individuals specifically. To date, no studies have delved into a wide range of sleep characteristics in transgender populations to determine risk factors for poor sleep quality. The purpose of this study was to use qualitative methods to explore the association between factors such as gender identity, mental health, and substance use and sleep health among a sample of transgender and gender non-conforming individuals in New York City. Methods: Forty in-depth interviews were conducted among an ethnically diverse group from July to August 2017 who identified as transgender and gender non-conforming. All interviews were transcribed, coded, and analyzed for emerging themes, including mental health affecting sleep, gender identity, and various coping mechanisms to improve overall sleep. Results: Our research found that 60% (n=24) of participants described various behaviors to improve sleep hygiene, including the use of either prescription or over-the-counter (OTC) sleep medication such as benzodiazepines, selective serotonin reuptake inhibitors (SSRIs), and antipsychotic pharmaceuticals. Additionally, 35% (n=14) of participants reported that their gender identity contributed to disruptive sleep, including feelings of gender dysphoria, self-consciousness about their physical body, the anxiety of identifying as transgender, and gender transition (hormonal therapy and gender-affirming surgery). Poor sleep health was also associated with mental illness, specifically anxiety and depression. Conclusion: Sleep health promotion interventions should be developed for transgender and gender non-conforming people, which would promote positive mental health, reduce the risk of pharmaceutical adverse events, and help alleviate psychosocial stress in this target population. Support (If Any): Dai, H., & Hao, J. (2017). Sleep deprivation and chronic health conditions among sexual minority adults. Behavioral Sleep Medicine, 1-15.